2012
DOI: 10.1007/s10853-012-6913-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements of the mechanical properties and thermal conductivity of carboxylated acrylonitrile butadiene rubber with the addition of graphene oxide

Abstract: Graphene oxide (GO)/carboxylated acrylonitrile butadiene rubber (xNBR) vulcanizates were prepared in this study by mixing exfoliated GO aqueous dispersion with xNBR latex. The GO monolayers were exfoliated from natural flake graphite by Hummers' method. This study shows that GO could be dispersed homogeneously in xNBR matrix up to 1.2 vol.%. Adding GO nanosheets has a great effect on the mechanical, thermal stability, thermal conductivity, and thermal diffusivity of GO/xNBR vulcanizates. With the incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 54 publications
6
55
0
Order By: Relevance
“…It is interesting to find that the elongation at break of NR/GO nanocomposite decreases with decreasing GO size. Previous studies also found that the addition of GO into rubber led to a decrease in the elongation at break of the composites, which is because the movement of the polymer chains is restricted by the interaction between the GO and polymer matrix [16,48]. Therefore, in our work, it can be understood that GO with smaller size have more number of contacts with NR, which in turn leads to stronger restriction on the rubber chains.…”
Section: Effects Of Go Size On the Mechanical Properties Of Nr/go Nansupporting
confidence: 58%
“…It is interesting to find that the elongation at break of NR/GO nanocomposite decreases with decreasing GO size. Previous studies also found that the addition of GO into rubber led to a decrease in the elongation at break of the composites, which is because the movement of the polymer chains is restricted by the interaction between the GO and polymer matrix [16,48]. Therefore, in our work, it can be understood that GO with smaller size have more number of contacts with NR, which in turn leads to stronger restriction on the rubber chains.…”
Section: Effects Of Go Size On the Mechanical Properties Of Nr/go Nansupporting
confidence: 58%
“…In most published papers, additives contained in nanofluids are usually zero dimensional nanoparticles or one dimensional carbon nanotubes or nanowires (Chandrasekaran et al, 2014;Kumaresan et al, 2012;Shaikh et al, 2008). Graphene oxide nanosheet is a two dimensional material with many unique physical, chemical and mechanical properties, which may cause to quite different thermophysical properties from other nanomaterials (Wang et al, 2013;Heo et al, 2012;Tasviri et al, 2013;Mehrali et al, 2013). To the best of our knowledge, there is no paper reporting the supercooling and nucleation behavior of nanofluids containing graphene oxide nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that owing to the large amount of oxygencontaining groups, graphene nanoribbon could uniformly disperse in matrix and had interactions with matrix, thus the thermal stability of SR was improved. Wang et al 15 reported that GO improved the thermal stability of carboxylated acrylonitrile butadiene rubber vulcanizates. It was attributed to the interactions between the rubber matrix and the fillers, which is connect with exfoliation, aspect ratio of GO, and the hydrogen bonding between GO and the polymer.…”
Section: Introductionmentioning
confidence: 99%